Integrating Peer Support Workers into Mental Health Programs - Sexsmith Chadwick, Samantha; Fahr, Heather; Maleski, Jytte (Journal of Recovery in Mental Health, 2024)
Objective: There is little known about the role of Peer Support Workers (PSWs) in mental health programming in Western Canada. To contribute to this body of knowledge, Canadian Mental Health Association – Calgary Region (CMHA Calgary) sought to clearly define and understand how PSWs could support mental health programming in a non-clinical way. Research Design and Methods: CMHA Calgary planned to integrate PSWs into all existing mental health programs. The integration of PSWs was piloted in the organization’s group counselling program to collect information and gain learnings that could be used to spread the initiative to all programs. The project team developed a developmental evaluation framework as a guide to collect feedback and understand the impact of the initiative. Qualitative data was collected from PSWs, counsellors, and program management using formal one-on-one interviews, anonymous surveys, and consensus building in group settings. This information was analyzed using a collaborative thematic analysis approach. This involved two reviewersworking together to analyze and identify themes within the data. Results: This project provided CMHA Calgary with information on how to integrate PSWs into all programs. The project further allowed for the development of program materials for future application. Conclusions: The results of this project contribute to the overall knowledge of PSWs in Western Canada and can be used by other organizations looking to integrate PSWs into mental health programming.